The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s13224-016-0920-0
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Cohort Study to Assess and Correlate the Maternal Periodontal Status with Their Pregnancy Outcome

Abstract: Background There is an overwhelming body of evidence strongly suggesting that periodontal infection may have a significant negative impact on pregnancy outcome in some women. The aim of this study was to determine the association between periodontal disease and preterm low birth weight of babies.Materials and Methods A total of 300 pregnant women, between 20 and 24 weeks of gestation i.e., second trimester, were considered for the study. The periodontal status was recorded using the following parameters: probi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
2
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 17 publications
0
11
2
5
Order By: Relevance
“…The results are similar to the findings reported by Buduneli et al and Lohana et al who reported that mothers who delivered PTLBW babies gained significantly less weight during the pregnancy. 12,15 The above results are contradictory to those reported by Romero et al who stated that BMI does not have significant relation to PTLBW. 16 The contradictory results of present study to Romero et al may be due to the difference in the population of study subjects.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…The results are similar to the findings reported by Buduneli et al and Lohana et al who reported that mothers who delivered PTLBW babies gained significantly less weight during the pregnancy. 12,15 The above results are contradictory to those reported by Romero et al who stated that BMI does not have significant relation to PTLBW. 16 The contradictory results of present study to Romero et al may be due to the difference in the population of study subjects.…”
Section: Discussioncontrasting
confidence: 81%
“…These results are similar to Lohana et al and Lopez et al who stated that there is no significant relation between education level and PTLBW babies. 3,12 The results are contradictory to those stated by Radnai et al and Davenport et al who reported that both maternal and paternal education influence, the birth weight of babies. 13,14 The current study demonstrates that with decrease in BMI, there was an increase in prevalence of PTLBW babies, this was due to babies nutritional status was hampered due to mother's inadequate nutritional determinants and lack of antenatal care.…”
Section: Discussioncontrasting
confidence: 63%
“…2 Studies in various populations have demonstrated strong association between periodontal diseases and adverse pregnancy outcomes such as preterm low birth weight (PTLBW). [3][4][5] to be associated with the occurrence of PTD, LBW and PTLBW 1,3,4 suggested is that periodontal infections serve as chronic reservoir of microorganisms that cause production of interleukins and prostaglandins which in turn induce preterm parturition. 2 Medical doctors are the ones who often deal with antenatal care (ANC).…”
Section: Introductionmentioning
confidence: 99%
“…По результатам проведённых многочис-ленных исследований, у беременных со сто-матологической патологией, главным образом воспалительными заболеваниями пародонта, возрастает риск развития синдрома задержки роста плода, преждевременных родов, рожде-ния детей с низкой массой тела, развития преэклампсии, повышения материнской смерт-ности. Данное заключение было сформировано при проведении крупных рандомизированных исследований в Америке и Европе [1], Канаде на 273 пациентках [2], Индии на 300 [3] и 790 [4] пациентках, микробиологическом и гисто-логическом исследовании в Нидерландах [5].…”
unclassified
“…По результатам метаанализа, относитель-ный риск развития преждевременных родов с рождением ребёнка с низкой массой тела при наличии хронического генерализованного па-родонтита (ХГП) у матери в гестационный пе-риод составляет 3,5 (доверительный интервал 1,5-7,9), установлено снижение частоты преж-девременных родов при лечении гингивита и ХГП во время беременности с 6 до 2% [4].…”
unclassified